Stochastic season-wide optimal production planning of virgin olive oil. (December 2018) - Cano Marchal, P.; Martínez Gila, D.; Gámez García, J.; Gómez Ortega, J.
Abstract: The quality and obtained quantity of Virgin Olive Oil is determined by the influence of the process variables during the production process based on the properties of the olives being processed. Since the quality of the olives evolve during the harvesting season, a relevant question is to systematically suggest when to harvest the olives in order to maximize the profit over the whole season. This work proposes a method to determine an optimal production plan for the whole harvesting season explicitly considering the stochastic nature of the problem, the uncertainty in the problem parameters and the information available at each step, and presents the results obtained in its application to different production scenarios.